Challenges of Implementing Consortium Strategy in Development Projects at ViAgroforestry, Kenya - Catherine A. Osoo; Vincent N. Machuki (European Scientific Journal, ESJ, 2019)
Consortium strategy involves an arrangement in which organizations develop, utilize and amalgamate structures, cultures, and operational systems to support competitiveness in delivery of service in a dynamic environment. This study sought to investigate challenges of implementing consortium strategy and measures to mitigate the challenges at ViAgroforestry, Kenya. Through a case study design both primary and secondary data were gathered through personal interviews and analysis of relevant documents respectively. Content analysis was used to analyze data. The study established that, both internal and external factors affected effective consortium strategy implementation at ViAgroforestry. The external factors that affected strategy implementation included social-cultural, political, economic, and technological factors. The internal factor included leadership and management styles, competency of employees among the partner organizations, lack of employee commitment to consortium operation, lack of adequate financial resources, unclear implementation guidelines and inconsistency in deployment of employees to support consortium. The mitigation measures to deal with the challenges include building employee competencies and confidence, setting up and reinforcing clear guidelines for selecting, recruiting and exiting partners in the consortium, mobilization of adequate financial resources, enhanced integration of Information Communication Technology (ICT) within the operating systems, and democratic style of management among partners. It was recommended that ViAgroforestry, Kenya should align organizational structure, provide adequate resources, build employee competencies and set and reinforce clear guidelines for operations while integrating ICT in its operations for effective consortium strategy implementation. In view of the limitations of the study, further research has been suggested on evaluating performance of consortium strategy implementation at ViAgroforestry, Kenya.